The cymothoid isopod Anilocra chromis is negatively associated with multiple metrics of host condition in the Caribbean damselfish Chromis multilineata - Jan-Alexis Barry; Kyle G. Jerris; Teresa R. Turner; Jenilee B. Robinson; Matthew D. Nicholson; Paul C. Sikkel (Marine Biology, 2026)
Parasitism is widespread among fishes in nature and can have significant impacts on individuals, populations, and communities. The family Cymothoidae includes over 380 species of parasitic isopods that infect a wide variety of host fishes, mostly in tropical and subtropical oceans. Despite their conspicuous nature, spatiotemporal patterns of infestation and effects on hosts have been studied for only a small percentage of species. The brown chromis ( Chromis multilineata ) is a common planktivorous damselfish associated with reefs in the tropical western Atlantic. Brown chromis are frequently infested with the large cymothoid isopod Anilocra chromis. In this study, we quantified the prevalence of infection among five sites and over two years in the US Virgin Islands (before and after major hurricanes). We further quantified the relationship between Anilocra infection status and the coinfection of other parasites as well as three metrics of potential impact: gonadal development, rate of food intake, and locomotion. Our results show that parasite prevalence differed significantly among sites. Additionally, while there was variation in coinfection with other parasites among sites, there was no relationship between the presence of Anilocra and the abundance of other parasites. There was a significant negative effect of Anilocra infection on male chromis gonads, feeding behavior (as determined by a decrease in bite-rates), and locomotion (as determined by an increase in fin-beats). Overall, these findings suggest that parasitism by Anilocra chromis is negatively associated with multiple metrics of fitness and health in host fishes, and thus likely has consequences at the population level.